Sharia supervision board, board independence, risk committee and risk-taking of Islamic Banks in Malaysia - Ramly, Zulkufly; Datuk Haji Mohamad Nordin, Nurusysyifa (International Journal of Economics and Financial Issues, 2018)
This paper investigates the moderating effects of Sharia Supervision Boards (SSBs) on the links between board independence and risk committee (RC) independence and Islamic banks’ (IBs) risk-taking in Malaysia from 2010 to 2015. The paper highlights four important findings: (1) SSB’s expertise in Sharia and banking-related areas lower credit risk, (2) higher board independence is likely to reduce credit risk when SSBs consist of Sharia advisors with expertise in Sharia and banking-related areas, (3) higher RC independence is likely to reduce credit risk when SSBs consist of Sharia advisors with expertise in Sharia and banking-related areas and (4) the reducing effect of RC on credit risk is conditional upon the higher participation of female Sharia advisors in SSBs. This study suggests that the resources in terms of the valuable experience that SSB advisors bring to IBs combined with the typical oversight mechanisms such as board independence and RC as suggested by corporate governance literature are beneficial to control risk-taking in the Malaysian IBs. Further, this paper demonstrates that integrating agency theory and resource dependence view in a corporate governance study produces a more meaningful result.